Uropathogenic Escherichia coli Isolates from Pregnant Women in Different Countries - Ramos, Nubia L.; Sekikubo, Musa; Thi Ngoc Dzung, Dang; Kosnopfel, Corinna; Kironde, Fred; Mirembe, Florence; Braunera, Annelie (Journal of clinical microbiology, 2012)
Urinary tract infection (UTI) is common during pregnancy and can be associated with negative outcomes for both the mother and fetus. Increased risk of infection among these patients has been attributed to physiological changes, and less focus has been placed on Escherichia coli, the most frequent causative agent. We investigated the virulence properties of isolates causing UTI in pregnant women in Sweden, Uganda, and Vietnam, as well as nonpregnant women in Sweden. Although phylogenetic group B2 was the most prevalent group, more Ugandan isolates belonged to group B1, associated with commensal strains, than isolates from other countries. Adherence to and invasion of urothelial cells, key events in the infection process, were low among group B1 isolates from pregnant Swedish women compared to those from nonpregnant patients. Similar levels of adherence and invasion were seen in isolates from pregnant women in Uganda and Vietnam. More biofilm was formed by group B2 isolates than by those belonging to group B1 and by Ugandan group B2 isolates than by those from pregnant Swedish and Vietnamese women. The antigen 43a-encoding gene, fluACFT073, was most prevalent among Ugandan isolates. Expression of the biofilm components, curli and cellulose, was low among all isolates. Multidrug resistance was more common among isolates from Uganda and Vietnam than among those from Swedish patients. We suggest that while bacterial virulence properties play an important role in UTI during pregnancy, physiological changes in the host may contribute more to the incidence of infection caused by less virulent E. coli.
Keywords: Uropathogenic Escherichia coli; Pregnant Women